Use of warfarin during pregnancy. - Abadi, Shirin (2002)
QUESTION: One of my patients, who has been taking warfarin for some time for treatment and prophylaxis of deep vein thrombosis, became pregnant due to failed contraception. I am unsure how to counsel her. Is there evidence that warfarin use during pregnancy is associated with fetal risk? ANSWER: If possible, warfarin therapy should be avoided during pregnancy. If warfarin therapy is essential, it should be avoided at least during the first trimester (because of teratogenicity) and from about 2 to 4 weeks before delivery to reduce risk of hemorrhagic complications. Unfractionated heparin or low molecular weight heparin could be substituted when appropriate because these agents do not cross the placenta and are considered the anticoagulant drugs of choice during pregnancy.